Synthesis and spectral Studies of Cu(II) Complexes of Substituted Schiff Bases - Mehta, B.H.; J. Jaya Murthy, Miss (Asian Journal of Chemistry, 2010)
Some novel complexes of Cu(II) with substituted Schiff bases as ligands are reported. The complexes invariably conform to the stoichiometry CuL2 and CuL. The ligands behave as bidentate one and the electronic absorption spectra, magnetic moment values and infrared spectral data in KBr disc indicate coordination number six to the Cu2+ ion. The low molar conductance values of all complexes show non-electrolytic nature of compexes. The overall stereochemistry has been assigned as octahedral or distorted octahedral.